2008
DOI: 10.1590/s0100-204x2008001100002
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane crop efficiency in two growing seasons in São Paulo State, Brazil

Abstract: -A conceptual framework for crop production effi ciency was derived using thermodynamic effi ciency concept, in order to generate a tool for performance evaluation of agricultural systems and to quantify the interference of determining factors on this performance. In Thermodynamics, effi ciency is the ratio between the output and input of energy. To establish this relationship in agricultural systems, it was assumed that the input energy is represented by the attainable crop yield, as predicted through simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0
24

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 15 publications
4
22
0
24
Order By: Relevance
“…As observed by Marin et al (2008), solar radiation had the highest determination coefficient variable (16%), which may be due to the fact that most of the sugarcane growing areas have occupied some of the best agricultural areas of São Paulo, in which yield-limiting factors have less influence. Therefore, the crop was able to respond to a potential yield-related variable, such as solar radiation (Bowen & Baethgen, 2002).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…As observed by Marin et al (2008), solar radiation had the highest determination coefficient variable (16%), which may be due to the fact that most of the sugarcane growing areas have occupied some of the best agricultural areas of São Paulo, in which yield-limiting factors have less influence. Therefore, the crop was able to respond to a potential yield-related variable, such as solar radiation (Bowen & Baethgen, 2002).…”
Section: Resultsmentioning
confidence: 84%
“…From 1990From /1991From to 1995From /1996, SYE oscillated around 0.45, as a result of the tough Brazilian macroeconomic conjuncture and of the unfavorable conditions for sugar and ethanol commercialization (Goldemberg & Lucon, 2007). Marin et al (2008), using the Doorembos & Kassan (1994) model, found values ranging from 0.38 to 0.43.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; where yield data (I.B.G.E., 2013) were paired with cumulative PAR derived from daily average solar irradiance (18.6 MJ m À2 day À1 ) (Marin et al, 2008), assuming PAR is 50% of total irradiance). Residuals of the relationships between NEE and PAR indicated that NEE was inhibited by high VPD and temperature, however, these relationships were not detectable during peak photosynthetic phases.…”
mentioning
confidence: 99%
“…The best estimates of sugarcane productivity are obtained when this model is adjusted and calibrated for the local climatic conditions (Barbieri & Silva, 2008;Oliveira et al, 2012). Other models have also been described to estimate sugarcane productivity for local conditions (Scarpari, 2002;Marin et al, 2008;Cuadra et al, 2012), emphasizing the model proposed by Scarpari (2002), which because working with the variables rainfall and air temperature is a good alternative to predict sugarcane productivity in the climatic conditions of Cerrado in the Center-West of Brazil.…”
Section: Introductionmentioning
confidence: 99%